PENERAPAN PEMBELAJARAN KOOPERATIF MODEL THINK PAIR AND SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN EKONOMI KELAS X IPS 2 DI MAN 3 MALANG - Istiqomah Istiqomah; Achmad Ali Wafa (Jurnal Pendidikan Ekonomi, 2017)
Cooperative learning model Think Pair and Share (TPS) is a cooperativelearning technique that requires students to think, respond to, and worktogether to achieve the learning objectives. The results of student learning isthe value achieved by students cognitively of the material on the Market andMarket Price Formation in Economy measured through test questionsprovided by the teacher is the matter of granting pre-activity and postactivitycycle I and II to measure cognitive domains. The approach in thisstudy used a qualitative approach, type of research is a class act. This studywas conducted two cycles, each cycle consisting of two meetings. Subjectsused were students of class X IPS 2 MAN 3 Malang. The instrument used inthis study is a matter of testing, observation checklist, field notes,documentation, and questionnaire. The results showed that by applying thelearning Think Pair and Share (TPS) can improve learning outcomes asindicated by the value of post-activity of students in cycle 1 students whopass as many as 21 students or equal to 70% with an average grade of 81.5.In the second cycle students who pass as many as 30 students or in otherwords the whole class X IPS 2 MAN 3 Malang completed. From theseresults it can be seen that the implementation of cooperative learning ThinkPair and Share can improve student learning outcomes.DOI: https://dx.doi.org/10.17977/UM014v10i12017p015